Process gas chromatographs : advanced design and trouble shooting - Waters, Tony (Consultant) (John Wiley & Sons, Inc., 2025)
"Process gas chromatography, established in the late 1950s, is used for separating and analyzing chemical compounds in the gas phase of industrial processes. Gas chromatograph instruments vaporize and distribute samples between a stationary and mobile phase, whereby a chemically inert gas carries molecules through a heated column. The aim in installing analyzers on-line is to obtain the analytical results with a response time that is comparable to process changes, thus using the information to take corrective action to optimize the process. As such, process GC is a complex application and optimum training is required for engineers who design and operate them."-- Provided by publisher.
"A companion volume of Process gas chromatographs (2020)" -- title page.
Keywords: Gas chromatography -- Equipment and supplies.; elektronické knihy; electronic books